ANALISIS PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN MENGGUNAKAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Dewi, Nuning Nurna (STIE Mahardhika, 2019)
The aim of this study is to examine the effect of leadership style and work environment to work motivation to improve employee performance. The approach used is quantitative parametric method of Structural Equation Model. The study object is the production employees of PT Suparma Tbk. The results showed leadership style has positive but not significant  effect on work motivation; work environment has positive and significant effect on employee motivation; leadership style has  negative but not significant effect on employee performance; the working environment is not significant positive effect on employee performance; and motivation has positive and significant effect on employee performance. Work Motivation as intervening variable (Y),  is able to be explained by exogenous variables leadership style variable (X1) and Work environment (X2) by 55.4%, and the remaining 44.6% is explaiened by variables outside the models. Whereas endogenous variables, employee performance (Z) which is explained by the work motivation variable (Y), work environment (X1), and the style of leadership (X2) amounted to 94.1%, and the remaining 5.9% is explained by variables outside the model. With the calculation of sub-structural equation 1 is Y = 0,053X_1 + 1,065X_2 + 0,833, and the calculation of substructural equation 2 is Z = -0,193X_1 + 0,529X_2 + 0,723Y + 0.338.